Application of nanomaterials against SARS-CoV-2: An emphasis on their usefulness against emerging variants of concern - Iqbal, Reema; Khan, Sadia; Ali, Haroon Muhammad; Khan, Maham; Wahab, Shahid; Khan, Tariq (Frontiers in Nanotechnology, 2022)
Researchers are now looking to nanomaterials to fight serious infectious diseases that cause outbreaks and even pandemics. SARS-CoV-2 brought chaos to almost every walk of life in the past two years and has challenged every available treatment method. Although vaccines were developed in no time against it, the most pressing issue was the emergence of variants of concern arising because of the rapidly evolving viral strains. The higher pathogenicity and, in turn, the higher mortality rate of infections caused by these variants renders the existing vaccines less effective and the effort to produce further vaccines a costly endeavor. While several techniques, such as immunotherapy and repurposed pharmaceutical research, are being studied to minimize viral infection, the fundamentals of nanotechnology must also be considered to enhance the anti-SARS-CoV-2 efforts. For instance, silver nanoparticles (AgNPs) have been applied against SARS-CoV-2 effectively. Similarly, nanomaterials have been tested in masks, gloves, and disinfectants to aid in controlling SARS-CoV-2. Nanotechnology has also contributed to diagnoses such as rapid and accurate detection and treatment such as the delivery of mRNA vaccines and other antiviral agents into the body. The development of polymeric nanoparticles has been dubbed a strategy of choice over traditional drugs because of their tunable release kinetics, specificity, and multimodal drug composition. Our article explores the potential of nanomaterials in managing the variants of concern. This will be achieved by highlighting the inherent ability of nanomaterials to act against the virus on fronts such as inhibition of SARS-CoV-2 entry, inhibition of RNA replication in SARS-CoV-2, and finally, inhibition of their release. In this review, a detailed discussion on the potential of nanomaterials in these areas will be tallied with their potential against the current and emerging future variants of concern.